Stress and Environmental Regulation of Gene Expression and Adaptation in Bacteria 2016
DOI: 10.1002/9781119004813.ch89
|View full text |Cite
|
Sign up to set email alerts
|

Acid Survival Mechanisms in Neutralophilic Bacteria

Abstract: Numerous commensal and pathogenic Gram-negative and Gram-positive bacteria are referred to as neutralophiles because they grow best at pH levels close to neutrality. Thus, exposure to harsh-to-mild acidic environments, such as those encountered in the digestive tract of animal hosts, in the phagosome of macrophages, in fermented foods, but also in the soil or in acid mine drainage, is a rather common encounter for neutralophiles during their life cycle. As a result, it is not surprising that most of them have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 171 publications
1
3
0
Order By: Relevance
“…S10) and should be positive for sufficiently acidic pH e . This prediction is consistent with observations that cells responds to acidic stress by directly or indirectly generating positive charge: some amino acids to are converted into more positively charged molecules and negatively charged glutamate is converted into neutral γ -aminobutyric acid [58, 59, 60].…”
Section: Resultssupporting
confidence: 91%
“…S10) and should be positive for sufficiently acidic pH e . This prediction is consistent with observations that cells responds to acidic stress by directly or indirectly generating positive charge: some amino acids to are converted into more positively charged molecules and negatively charged glutamate is converted into neutral γ -aminobutyric acid [58, 59, 60].…”
Section: Resultssupporting
confidence: 91%
“…Moreover, other work using acid‐tolerant bacteria (background described in Eguchi and Utsumi and in Pennacchietti et al . ) showed that the Pd(0) deposition and catalytic activity of the resulting ‘bio‐Pd(0)’ was indistinguishable in parental and acid‐resistant cells of E. coli (L. Zajac, A.J. Murray, P.A.…”
Section: Discussionmentioning
confidence: 99%
“…A paradigmatic case of both the negative and positive impacts that the metabolic changes induced by acid stress responses may have on human health outcomes is exemplified by the various amino acid decarboxylases that are induced by cell exposure to acid pH. Decarboxylation pathways are activated in acid conditions as they catalyze the conversion of an amino acid into a biogenic amine, generating carbon dioxide and consuming a proton, thus contributing to the maintenance of the intracellular pH and improved survival at low pH (Pennacchietti et al 2016 , Lund et al 2020 ). On the negative side, some biogenic amines produced by micro-organisms through the action of decarboxylases, such as histamine (from His), tyramine (from Tyr), 2-phenylethylamine (from Phe), tryptamine (from Trp), putrescine (from ornithine or through the agmatine deiminase pathway, which follows the decarboxylation of arginine to agmatine), and cadaverine (from Lys), can cause several adverse reactions to consumers, such as tingling tongue, rash, vomiting, diarrhea, burning sensation, headache and dizziness, nausea, palpitations, or breathing difficulties.…”
Section: Low Ph As a Key Parameter In Food Preservation Processing An...mentioning
confidence: 99%